Bukit Duri Riverbank Green Settlement - Avinda Tasha Astree Vielandy; F. X. Teddy Badai Samodra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2017)
In urban areas like Jakarta, the rapid urbanization increases the high level of housing needs that leads to the emergence of slums. The way the governments solve this problem is seen as inhumane and not viable at all. The solution proposed by the government actually creates new slum problems. The objective of this project is to upgrade the riverbank slum into a green settlement with improved housing by implementing six principles of Green Architecture into the design. Field measurement and interview were conducted to obtain data for simulation using Ecotect Analysis and ANSYS Fluent software. The result emphasized that